Auctions, risk and the WACC. How auctions and other risk factors impact renewable electricity financing costs - Barbara Breitschopf; Abigail Alexander-Haw (Energy Strategy Reviews, 2022)
Renewable electricity procurement auctions (RE auctions) have received much attention for their potential efficiency in reducing the cost of support levels associated with renewable electricity (RE). However, very little attention has been paid to their impact on financing costs. This is problematic as financing costs are central for investors when deciding whether to invest in renewable technologies, and can thus be critical for effective RE deployment. We applied a multi-level risk perspective that comprises country specific, renewable sector related and project related risks. This risk-based approach was used to identify the effect of RE auction implementation on financing costs whilst including relevant further risks. Using a 2-level cross classified multilevel model, it was demonstrated that, contrary to politician's fears, the implementation of auctions does not increase financing costs. In addition, technology type and the state of development of the finance sector in the specific country were revealed as having a very significant impact on the cost of capital. Our findings indicate that in order to promote the deployment of RE technologies, policy makers should not focus on whether or not to deploy auctions, but on general financial conditions, the type of remuneration scheme, and risk mitigation in general.